Comparing the Assessment of Omentin-1 and Chemerin Levels in Acute Myocardial Infarction in Patients with Diabetes and Healthy Subjects - S Sami Ali (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul)
Background and Objective: Acute myocardial infarction (AMI) is a serious and life-threatening disease caused by a sudden blockage of blood flow in the heart muscle. According to the contradictory results in studies investigating the levels of chemerin (with the role of enhancing inflammation) and omentin-1 (with anti-inflammatory properties) in patients with diabetes, this study aims to compare the levels of omentin-1 and chemerin in patients with acute myocardial infarction (AMI) with and without diabetes and its relationship with vascular lesions, HbA1c, blood pressure, CRP and serum creatinine. Methods: In this cross-sectional study, a total of 80 AMI patients were randomly included in this study with the age range of 37-79 years old, categorized according to the presence (26 patients) or absence (54 patients) of diabetes and the number of arteries with lesions. The levels of omentin-1 and chemerin were measured using ELISA kits, and correlations between the adipokines and other parameters were evaluated using Pearson correlation analysis. ROC curve analysis was performed to assess the diagnostic value of omentin-1 and chemerin in distinguishing AMI patients with and without diabetes. Findings: The demographic characteristics of patients of the two groups, including age, systolic and diastolic blood pressure showed non-significant differences. The levels of omentin-1 were not significantly different between AMI patients with and without diabetes, while chemerin levels were significantly higher in AMI patients with diabetes (1.212±0.232) as compared to the AMI patients without diabetes (0.72±0.116) (p<0.01). The AUC values for omentin-1 and chemerin were 0.603 and 0.640, respectively, in differentiating AMI patients with and without diabetes. There was no significant difference in the levels of both hormones according to the number of arteries with lesions. Significant correlations were found between omentin-1 and chemerin levels and HbA1c (p<0.05), while no significant correlations were found with blood pressure, CRP, or serum creatinine. Conclusion: The results of this study showed that chemerin can be a useful biomarker for identifying patients with myocardial infarction with diabetes.